Relative contributions of emphysema and airway remodelling to airflow limitation in COPD: Consistent results from two cohorts. Issue 4 (18th March 2015) - Tho, Nguyen Van; Ryujin, Yasushi; Ogawa, Emiko; Trang, Le Thi Huyen; Kanda, Rie; Goto, Kenichi; Yamaguchi, Masafumi; Nagao, Taishi; Lan, Le Thi Tuyet; Nakano, Yasutaka
Abstract Background and objective The relative contributions of emphysema and airway remodelling to airflow limitation remain unclear in chronic obstructive pulmonary disease (COPD). We aimed to evaluate the relative contributions of emphysema and airway wall thickness measured by quantitative computed tomography (CT) to the prediction of airflow limitation in two separate COPD cohorts. Methods Pulmonary function tests and whole‐lung CT were performed in 250 male smokers with COPD, including 167 from University Medical Center at Ho Chi Minh City, Vietnam, and 83 from Shiga University of Medical Science Hospital, Japan. The same CT analysis software was used to measure the percentage of low attenuation volume (%LAV) at the threshold of −950 Hounsfield units and the square root of wall area of a hypothetical airway with an internal perimeter of 10 mm (Pi10). The standardized coefficients in multiple linear regressions were used to evaluate the relative contributions of %LAV and Pi10 to predictions of FEV1/FVC and FEV1% predicted. Results Both %LAV and Pi10 independently predicted either forced expiratory volume in 1 s/forced vital capacity (FEV1/FVC) or FEV1% predicted (P ≤ 0.001 for all standardized coefficients). However, the absolute values of the standardized coefficients were 2−3 times higher for %LAV than for Pi10 in all prediction models. The results were consistent in the two COPD cohorts. Conclusions %LAV predicts both FEV1/FVC and FEV1 better than Pi10 in patients with COPD. Thus, emphysema may make a greater contribution to airflow limitation than airway remodelling in COPD.